Canadian stroke best practice recommendations: Stroke rehabilitation practice guidelines, update 2015. Issue 4 (June 2016) - Hebert, Debbie; Lindsay, M Patrice; McIntyre, Amanda; Kirton, Adam; Rumney, Peter G; Bagg, Stephen; Bayley, Mark; Dowlatshahi, Dar; Dukelow, Sean; Garnhum, Maridee; Glasser, Ev; Halabi, Mary-Lou; et al.
Stroke rehabilitation is a progressive, dynamic, goal-orientated process aimed at enabling a person with impairment to reach their optimal physical, cognitive, emotional, communicative, social and/or functional activity level. After a stroke, patients often continue to require rehabilitation for persistent deficits related to spasticity, upper and lower extremity dysfunction, shoulder and central pain, mobility/gait, dysphagia, vision, and communication. Each year in Canada 62, 000 people experience a stroke. Among stroke survivors, over 6500 individuals access in-patient stroke rehabilitation and stay a median of 30 days (inter-quartile range 19 to 45 days). The 2015 update of the Canadian Stroke Best Practice Recommendations: Stroke Rehabilitation Practice Guidelines is a comprehensive summary of current evidence-based recommendations for all members of multidisciplinary teams working in a range of settings, who provide care to patients following stroke. These recommendations have been developed to address both the organization of stroke rehabilitation within a system of care (i.e., Initial Rehabilitation Assessment; Stroke Rehabilitation Units; Stroke Rehabilitation Teams; Delivery; Outpatient and Community-Based Rehabilitation), and specific interventions and management in stroke recovery and direct clinical care (i.e., Upper Extremity Dysfunction; Lower Extremity Dysfunction; Dysphagia and Malnutrition; Visual-Perceptual Deficits; Central Pain; Communication; Life Roles). In addition, stroke happens at any age, and therefore a new section has been added to the 2015 update to highlight components of stroke rehabilitation for children who have experienced a stroke, either prenatally, as a newborn, or during childhood. All recommendations have been assigned a level of evidence which reflects the strength and quality of current research evidence available to support the recommendation. The updated Rehabilitation Clinical Practice Guidelines feature several additions that reflect new research areas and stronger evidence for already existing recommendations. It is anticipated that these guidelines will provide direction and standardization for patients, families/caregiver(s), and clinicians within Canada and internationally.